2017
DOI: 10.20418/jrcd.vol3no2.270
|View full text |Cite
|
Sign up to set email alerts
|

The pilot study of role of electrical cardiometry in non-invasive assessment of hemodynamic parameters in patients with pulmonary arterial hypertension (RCD code: II-1A.1)

Abstract: Background: Electrical cardiometry (EC) technique could estimate cardiac output (CO), cardiac index (CI) and other parameters related to cardiac contractility and fluid status by measuring the thoracic electrical bioimpedance. We hypothesized that EC could assess right ventricle (RV) hemodynamic function in patients diagnosed with pulmonary arterial hypertension (PAH). Results: In our pilot study, enrolling 23 PAH patients, we observed a significant correlation (r = 0.71; p <0.001) between thermodilution CO me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[ 15 18 ] However, with respect to adult patients, there has been significant heterogeneity of outcomes. [ 19 22 ] A number of studies have reported unacceptable intraoperative accuracy and interchangeability of EV with other standard methods. [ 14 , 23 , 24 ] In our study, several factors could have contributed to the observed poor interchangeability between the ICON system and TTE.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 18 ] However, with respect to adult patients, there has been significant heterogeneity of outcomes. [ 19 22 ] A number of studies have reported unacceptable intraoperative accuracy and interchangeability of EV with other standard methods. [ 14 , 23 , 24 ] In our study, several factors could have contributed to the observed poor interchangeability between the ICON system and TTE.…”
Section: Discussionmentioning
confidence: 99%
“…EC is frequently suggested as a method for measuring hemodynamics that is reliable, safe, and accurate. also has FDA validation and approval for use in newborns [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%